Causal relationships of obesity on musculoskeletal chronic pain: A two-sample Mendelian randomization study - Chen, Xiaoqing; Tang, Haifeng; Lin, Jinding; Zeng, Rongdong (Frontiers in Endocrinology, 2022)
Background: The association between obesity and chronic pain has attracted much attention these days, however, the causal relationship between them is uncertain. Hence, this study performed a mendelian randomization (MR) analysis to investigate the causal effects of body mass index (BMI), waist circumference (WC), hip circumference (HC), waist-to-hip ratio (WHR) on knee pain, hip pain and back pain. Materials and methods: The summary data for obesity and chronic pain came from the Genome-wide association study datasets. Significant and independent (P < 5×10-8; r2<0.001, kb=10000) single-nucleotide polymorphisms were extracted for MR analysis. The inverse variance weighted (IVW) and other methods were used for MR analysis, while sensitivity analyses were conducted to test the reliability and stability. Results: The positive causal effects of BMI on knee pain (OR: 1.049; 95% CI: 1.034 to 1.063; P=9.88×10-12), hip pain (OR: 1.034; 95% CI: 1.024 to 1.044; P=1.38×10-12), and back pain (OR: 1.022; 95% CI: 1.007 to 1.038; P=0.004) were observed. WC and HC were also positively associated with knee pain (WC: OR: 1.057; 95% CI: 1.041 to 1.072; P=1.54×10-13; HC: OR: 1.034; 95% CI: 1.017 to 1.052; P=1.32×10-4) and hip pain (WC: OR:1.031; 95% CI: 1.020 to 1.042; P=2.61×10-8; HC: OR: 1.027; 95% CI: 1.018 to 1.035; P=5.48×10-10) but not back pain. No causal relationship was found between WHR and chronic pain. The results were robust according to sensitivity tests. Conclusions: This study revealed that BMI was positively related to knee, hip and back pain, WC and HC were positively associated with knee and hip pain, while WHR was not related to any type of the chronic pain.